Factors associated with the non-use of condoms among young people: a systematic review protocol - Bossonario, Pedro Augusto (2022)
Objective: To identify and analyze the factors associated with not using condoms among the young population. Method: A search for publications, selection, and data extraction from relevant articles will be conducted following the stage of elaborating the guiding question, in addition to the analysis and synthesis of evidence. The PEO strategy (person, exposure, and outcome) was used to elaborate the research question: “What are the factors associated with the non-use of condoms among young people?” The databases will be searched through controlled and free vocabulary, previously researched and related to the studied subject. Six databases will be considered for the search for publications, one referring to the gray literature. After obtaining the results, the studies will be exported to the Rayyan QCRI software program to exclude duplicate materials and publications will be selected by two independent reviewers. Observational-analytical studies will be included. The selected articles will be read in full, the data will be extracted using a structured form, the methodological quality analyzed, and finally, a narrative and quantitative synthesis of the obtained results will be performed.